Aerodynamic Noise Characterization of a Full-Scale Wind Turbine through High-Frequency Surface Pressure Measurements. Issue 5 (October 2015) - Bertagnolio, Franck; Madsen, Helge Aa.; Bak, Christian; Troldborg, Niels; Fischer, Andreas
The aim of this work is to investigate and characterize the high-frequency surface pressure fluctuations on a full-scale wind turbine blade and in particular the influence of the atmospheric turbulence. As these fluctuations are highly correlated to the sources of both turbulent inflow noise and trailing edge noise, recognized to be the two main sources of noise from wind turbines, this work contributes to a more detailed insight into noise from wind turbines. The study comprises analysis and interpretation of measurement data that were acquired during an experimental campaign involving a 2 MW wind turbine with a 80 m diameter rotor as well as measurements of an airfoil section tested in a wind tunnel. The turbine was extensively equipped in order to monitor the local inflow onto the rotating blades. Further a section of the 38 m long blade was instrumented with 50 microphones flush-mounted relative to the blade surface. The measurements of surface pressure spectra are compared with the results of two engineering models for trailing edge noise and for turbulent inflow noise. The measured pressure fluctuations are related to the local inflow angle and are also compared to measurements in a wind tunnel on a copy of the blade section of the full scale blade. Computational Fluid Dynamics calculations were conducted to investigate the influence of the inflow conditions on the airfoil and blade sections aerodynamics and aeroacoustics. Comparisons between measurement data and model results show the influence of atmospheric turbulence. The different noise generation mechanisms can be identified and the influence of various parameters can be consistently reproduced by the models.